Enzymatic and structural characterization of new PLA2 isoform isolated from white venom of Crotalus durissus ruruima - Diz Filho, E. B. S. [UNESP]; Marangoni, S. [UNESP]; Toyama, D. O.; Fagundes, F. H. R. [UNESP]; Oliveira, S. C. B. [UNESP]; Fonseca, F. V. [UNESP]; Calgarotto, A. K.; Joazeiro, P. P.; Toyama, M. H. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
This work reports the structural and enzymatic characterization of a new sPLA2 from the white venom of Crotalus durissus ruruima, nominated PLA2A. The homogeneity of the PLA2A fraction and its molecular mass were initially evaluated by SDS-PAGE and confirmed by MALDI-TOF spectrometry, indicating a molecular mass of 14,299.34 Da. Structural investigation, through circular dichroism spectroscopy, revealed that PLA2A has a high content of alpha helix and beta-turn structures, 45.7% and 35.6% respectively. Its amino acid sequence, determined by Edman degradation and de novo amino acid sequencing, exhibited high identity to PLA2 Cdt F15 from Crotalus durissus terrificus. The enzymatic investigation, conducted using the synthetic substrate 4-nitre-3-(octanoyloxy)benzoic acid, determined its V(max) (7.56 nmoles/min) and K(M) (2.76 mM).Moreover, PLA2A showed an allosteric behavior and its enzymatic activity was dependent on Ca(2+). Intrinsic fluorescence measurements suggested that Ca(2+) induced a significant increase of PLA2A fluorescence, whereas its replacement for Mg(2+), Mn(2+), Sn(2+) and Cd(2+) apparently induced no structural modifications. The optimal pH and temperature for the enzymatic activity of PLA2A were 8.4 and 40 degrees C, respectively, and the minimal concentration of p-BPB and crotapotin that significantly inhibited such activity was 0.75 mM and 0.4 mu M, respectively. In addition, PLA2A showed a significant antibacterial effect that was not strictly dependent on the enzymatic activity of such sPLA2. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Crotalus durissus ruruima; Calcium binding; Venom; PLA2; Calcium binding loop